Emotional Intelligence and Academic Achievement of University Students - Mushtaq Ahmad, Asghar Ali,Bakhtawar Tariq (PJE, 2023)
This research was conducted to explore the emotional intelligence of university students and its relationship with their academic achievement. Through multi stage random sampling technique sample of 400 students of undergraduate (BS) final semester was selected including 160 males and 240 females 14 departments out of 7 faculties of university of Sargodha main campus.